From great athlete to great coach: self-reflection and past performances as predictors of coaching effectiveness of US rowing coaches - Kiosoglous, C. (2010)
Great coaches produce exceptional results by getting the best out of the people and resources in their environment. A coach`s survival depends on learning from each experience as coaching is a complex, dynamic and multifaceted process where one can`t be sure if results will go according to plan (Jones & Wallace, 2005). More money is being spent than ever before on developing more professional and effective training systems to maximize athletic performances (Whitson, 1998). The commercialization of the Olympic Games has generated record prosperity that benefits each successful nation pursuing Olympic success (Rosner & Shropshire, 2004). But Olympic medals are becoming even more difficult to win through the internationalization of sport (Bernard & Busse, 2004). Medals won determine how a coach is evaluated and the financial support received (Mallett & Côté, 2006). For coach educators developing more qualified coaches who are more adaptable to the pressures of the competitive coaching environment is paramount. The literature has been extensively examined based on this research question: to what extent is coaching success predicted by a coaches` ability to self-reflect on past experiences? The purpose of this study is to explore the hypothesis that a highly self-reflective coach with a successful athletic and coaching past could predict future coaching success